Why is 'Why' Unique? Its Syntactic and Semantic Properties - Soare, Gabriela; Bocci, Giuliano; Bonan, Caterina; Buell, Leston Chandler; Catasso, Nicholas; Cheng, Lisa Lai-Shen; Corver, Norbert; Cruschina, Silvio; Doron, Edit; Endo, Yoshio; Irurtzun, Aritz; Rizzi, Luigi; et al. (Studies in generative grammar ;, 2021)
Why is 'Why' Unique? Its Syntactic and Semantic Properties considers the behaviour of this peculiar wh-element across many different languages, including Ewe, Trevisan, Italian, Basque, German, Dutch, Cantonese, Mandarin, English and Hebrew. In ten original chapters, the authors explore various aspects of why-questions, such as the way why interacts with V2 constructions in Basque, with a subject clitic in Trevisan or how its morpho-syntactic make-up determines its merge position in Ewe, to mention but a few. Furthermore, a clear-cut distinction is established between high and low reason adverbials which are subsequently examined in why-stripping environments in Dutch. Beyond why proper, the book explores a special class of wh-expressions in some in-situ languages which give rise to unexpected why-construals with a touch of whining force. The objective is to explain the unusual syntactic position of these wh-expressions as well as their association with peculiar pragmatics. The questions are addressed for Cantonese: are what-initial sentences genuine questions? To what extent are Cantonese what-initial sentences similar to how-initial sentences in Mandarin? Beside these what-as-why questions, a special class of rhetorical questions, the doubly-marked interrogatives in Hebrew, come under scrutiny. Why is 'why' unique also concerns the interface with prosody and several experimental studies investigate precisely this aspect.